GlamHub Redefining Beauty and Fashion Retail through Digital Innovation and Consumer-Centric Strategies - Rathi B.,; Sreedhanya C,; Sunitha S, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Beauty provides an online way of reservation cosmetic services and also provides a window for customers for their selected services. GlamHub is an online platform that serves as a centralized interface connecting users with various beauty and styling service providers and product vendors. Users can book appointments with parlors, makeup artists, mehandi artists, and rental jewellery and costume shops, as well as order beauty products directly through the platform. The system includes features such as appointment scheduling, complaint resolution, product ordering, and multimedia content showcasing the work of service providers. GlamHub provides access to a diverse range of beauty service providers, including both established beauty parlors and individual artists or renters.
Keywords: Glamhub; reserveor; hassle; vibrant; salon; spa